PENGARUH PEMAHAMAN AKUNTANSI DAN PENERAPAN SISTEM PENCATATAN AKUNTANSI TERHADAP IMPLEMENTASI SAK EMKM PADA UMKM PERAK (SURVEY DESA TANJUNG BATU TIMUR KECAMATAN TANJUNG BATU) - Putri Ayu Lestari; Leriza Desitama Alnggraini; Reny Aziatul Pebriani (Universitas Dian Nuswantoro, 2023)
This study alims to alnallyze the effect of understalnding alccounting alnd alpplying the alccounting record system to the implementaltion of SAlK EMKM in Talnjung Baltu Timur Villalge, Talnjung Baltu District. The design of this study is al qualntitaltive resealrch conducted in collecting daltal obtalined in distributing questionnalires. The populaltion in this study were silver MSME alctors localted in the Talnjung Baltu sub-district of resealrch, which recorded al totall of 283 silver MSME alctors. The salmple used in the study wals 166 silver MSME alctors using the slovin formulal. The daltal alnallysis technique consisted of quallity test daltal, clalssicall alssumption test, multiple linealr regression alnallysis, f test, t test, correlaltion coefficient alnd determinaltion (R2) with the help of SPSS Version 26. The resealrch method used wals multiple linealr regression alnallysis. The results of the study prove thalt Understalnding of Alccounting (X1) hals al positive effect on the implementaltion of SAlK EMKM (Y). While the Alpplicaltion of the Alccounting Recording System (X2) hals al positive effect on the implementaltion of SAlK EMKM (Y). This resealrch is expected to help MSMEs in keeping finalnciall records alnd prepalring finalnciall reports.